外科手术任务负荷指数量表的汉化 及信效度检验. - 温晓萌; 韩小云 (Chinese Nursing Research, 2025)
Objective: To translate the Surgery Task Load Index(SURG-TLX) into Chinese and validate its reliability and validity, while employing network analysis to examine the structural relationships between SURG-TLX and the NASA Task Load Index (NASA-TLX). Methods: The Brislin translation model was adopted for forward and back translation of SURG-TLX, followed by cross-cultural adaptation through expert panel discussions and a preliminary survey. From October 2022 to May 2023, 639 surgical healthcare professionals from five tertiary grade A hospitals in Changzhou city were surveyed to assess the scale's reliability and validity. Results: The Chinese version of SURG-TLX consisted of six items. The scale-level content validity index(S-CVI) was 0.920, while item-level content validity indices(I-CVI) ranged from 0.800 to 1.000. The Cronbach's α coefficient was 0.886. The test - retest reliability was 0.801. Scores from the Chinese SURG - TLX showed a positive correlation with NASA-TLX scores(P< 0.001). Network analysis revealed strong associations between "mental demand" and "task complexity" in SURG-TLX, whereas "mental demand" and "physical demand" were closely linked in NASA-TLX. Conclusions: The Chinese version of SURG-TLX demonstrates good reliability and validity, making it an effective tool for assessing surgical task load, particularly in measuring task complexity, intraoperative distractions/interruptions, and situational stress among surgical healthcare professionals.